Water Resources Management in Darfur (University of Khartoum Engineering Journal, 2022)
The Darfur region is suffering from severe water shortage especially in the main urban centers with large concentration of internally displaced people (IDP) and areas of contact between pastoralists and farmers. That is why it has been widely circulated that the Darfur conflict was initiated by competition over stressed natural resources especially water. The Darfur Joint Assessment Mission (D-JAM, 2004) has specially pointed out to the importance of water as a determinant factor for sustainable recovery, development and peace in the region. Any plans for re-settlement require detailed assessment of water resources including water demand for various uses and provision of water supply from reliable sources taking into consideration strategies that ensure sustainability and rational management.This paper summarizes the results of assessment of surface (Wadis) and groundwater resources and rainwater harvesting potential in Darfur together with assessment of current and future needs for various water uses. Directions for strategic planning and management of water resources are also proposed through pilot projects at targeted areas. These projects include water harvesting, groundwater development, management of aquifer recharge in alluvial and fractured aquifers, conjunctive use of surface and groundwater and integrated watershed management in Wadi systems. The paper also outlines the urgent need for capacity development, research and development, monitoring networks and water information system. Water governance is an important issue which is also tackled in the paper by reviewing the current governance set-up and proposed directions for improvement. The results indicate that though there is a great stress on the readily available water resources in Darfur leading to the current conflict, it is found that there are enough water resources to meet current and future needs. However, harnessing these resources requires significant external and national funding, but this would be only a marginal portion of the cost paid by the UN for its peace keeping force and would certainly lead to peace in a faster and more sustainable way.